Questioning the Public Open Space Quality in Baykal District in Famagusta - Hadisi, Amir (Eastern Mediterranean University (EMU) - Doğu Akdeniz Üniversitesi (DAÜ), 2018)
Urban design deals with making connections between human, places, movements and urban configurations, milieu and the built original. The urban design is beneficial in many fields of place making, environmental proctorship, social balance and economic livability. In Famagusta, there is a problem to find which type of public open spaces are in their own characteristic and function. This study was focused on public open spaces in various viewpoints of urban design in the physical perspective in Baykal area in Famagusta, North Cyprus. Public open space which going to be analysis, classifying by the author to three parts: parks, streets, and squares. The major problem of this study is, some of the public open spaces areas haven’t any character for example, squares and streets, they all uses only for traffic function. And for parks there is not well designed to increase the life quality. This study focuses on applying urban design as a tool for determination of new designs and criteria to provide a fabric and attractive neighborhood to improve physical quality of public open spaces and also improve the physical characteristic of these public open spaces. The essential question in this part is, which part of public open spaces haven’t any character and how urban design can serve as a tool to improve the function of Baykal urban public open space. Generally, a public space is a place that is accessible to the public at any time of day, such as parks, street, squares and etc. These spaces all serve different functions, and can easily just be seen in spatial terms. Actually, this thesis is going to concentrate on street, square and parks because these three-public space is very important and essential. Lastly as a case of this study focused on Baykal district to assets public open spaces in terms of physical characteristic. In this research author classified the component of public open space to three part which are, square, street and parks and analyzing these component of each elements.

ÖZ: Kentsel tasarım insan mekan, ve kentsel konfigurasyonlar ile ilgili bağlantıları kurar. Ayrıca kentsel tasarım mekan yaratıma, çevre koruma, sosyal dengeyi oluşturma ve ekonomik canlılığın yartaılmasında önemli rol oynar.. Mağusa’da kamusal açık alanlar fonksiyon ve karakter tanımı açısından zayıftır. Bu çalışmada Mağusadaki Baykal bölgesinde kamusal açık alanların özellkile sokaklar ve meydanların tanımsız olduğu ve sadece araç tarfiğinin öncelikli mekanlar olarak kullanıldığı öncelikli problem olarak saptanmıştır. Bunun yanında parkların ise atıl durumdan kullanılmadığı diğer problemler arasındadır. Bu çalışma, Kuzey Kıbrıs, Mağusa kenti Bayakal Bölgesindeki, kamusal açık alanların farklı bakış açıları ile fiziksel formunun değerlendirmesini hedefler. Kamusal açık alanlar, yazar tarafından üç bölümde ele alınır, bunlar; parklar, sokaklar ve meydanlardır. Bu çalışma farklı yazarların kamusal açık mekan (meydanlar, sokaklar ve parklar) ile ilgili teorilerinin ele alındığı ve değerlendirildiği bir çalışmadır. Bu kapsamda farklı görülşlerin sentezi yapılarak çalışmaya ışık tutacak teorik kısım oluşturulacaktır. Bu çalışma, kentsel tasarım boyutunda kamusal açık mekanların- meydan, sokak,park- fiziksel açıdan oluşturulacak kriterler ile ele alınmasını ve değerlendirilmesini hedefler. Çalışmaya ışık tutacak en önemli araştırma sorusu; kamusal açık mekanların karakterini belirlemek için fiziksel formun analizi bu alanların kalitesini artırmak için bir araçmıdır? Bu tez, kamusal açık mekan olgusu kapsamında meydan, sokak ve parkların fiziksel formlarının analizine odaklanır. Bu mekanlar için değerlendirme kriterlerin belirlendikten sonra Mağusa Baykal bölgesindeki kamusal açık alan olarak nitelendirililen meydanlar, sokaklar ve parkların fiziksel formunun değerlendirmesi ise örneklem olarak bu çalışma kapsamında seçilmiştir. Örneklemde Meydanların, sokakların ve parkların elemanları ve bileşenleri belirlenmiş ve oluşturulan değerlendirme kriterlerlerine gore analizi ve değerlendirilmesi yapılmıştır.
Master of Science in Urban Design. Thesis (M.S.)--Eastern Mediterranean University, Faculty of Architecture, Dept. of Architecture, 2018. Supervisor: Assist. Prof. Dr. Nevter Zafer Comert.
Keywords: Architecture; Urban Design; Urban Design--Public Open Spaces--Baykal, Famagusta (Cyprus, North); Urban Design--City Planning--Historical Towns--Famagusta(Cyprus, North); Public open space; squares; streets; parks; Baykal Neighborhood